Detoxification mechanisms of nickel sulfate in nematode Caenorhabditis elegans. (December 2020) - Tang, Bowen; Williams, Phillip L.; Xue, Kathy S.; Wang, Jia-Sheng; Tang, Lili
Abstract: Nickel is the most prevailing metal allergen with the highest sensitization rate among the "TOP 25" contact allergens and can affect about 15% of the human population. It is an essential trace metal in plants, animals, and humans. However, the environmental levels of nickel are considerably higher than what is needed for human life. Exposure to high levels of nickel can lead to skin allergies, lung fibrosis, and carcinogenesis. Few existing studies have closely examined the toxicity of nickel, let alone investigated the effective detoxification pathways. Here, we developed a high-throughput screening platform to comprehensively evaluate the nickel toxicity in wild-type C. elegans and explore the underlying detoxification mechanisms in transgenic nematodes. We demonstrated that nickel exerted multiple toxic effects on growth, brood size, feeding, and locomotion in C. elegans . Of which, brood size is the most sensitive endpoint. Nickel was found to first bind to phytochelatin (PC) after entering the worms' body and this PC-Ni complex was further transported by the ABC transporter, CeHMT-1, into the coelomocytes for further detoxification. Our study also demonstrated that the high-throughput screening platform is a promising system for evaluation and investigation of the ecological risks of heavy metals. Highlights: NiSO4 effected growth, brood size, feeding, and locomotion in N2 C. elegans . Of the 4 tested endpoints, brood size is the most sensitive endpoint. Nickel absorbed by the worm and forms the PC-Ni complex with phytochelatin. The PC-Ni complex were transported by HMT-1 into coelomocytes for detoxification.